Echinococcus granulosus antigens activate different metabolic pathways in bone marrow-derived dendritic cells - Chop, Maia (2024)
Background: Activation of bone marrow-derived dendritic cells (BMDCs) by inflammatory stimuliinduces a metabolic shift from oxidative phosphorylation (OXPHOS) to glycolysis, which is directlyrelated to the effectiveness of the immune response.Objectives: This study aimed to determine whether laminar layer (pLL) or hydatid fluid (HF) purifiedfrom Echinococcus granulosus can modify cellular metabolism.Methods: HF and pLL were collected from cysts. BMDCs were obtained from CF-1 mice and cultured incomplete RPMI medium. Mitochondrial metabolic state was evaluated by confocal microscopy andFACS using the probe JC-1. Oligomycin and 2-deoxy-D-glucose (2DG) were used as inhibitors.SEAHORSE and SCENITH assays were performed.Results: Morphological analysis of HF-stimulated BMDCs showed a decrease in mitochondria number,total area, perimeter, branches and junctions compared to the control. Cells stimulated with pLLexhibited similar behavior to LPS-treated cells, with a predominance of polarized mitochondria. In HFstimulated cells, a significant decrease in the high/low fluorescence ratio was observed by FACS, whichincreased upon 2DG treatment. No major changes were observed in pLL-stimulated cells (n = 3,**p<0,01, ****p<0,0001 HF or pLL vs. control). SEAHORSE assays revealed that the basal oxygenconsumption rate (OCR) was lower in HF-stimulated BMDCs than in the control. The extracellularacidification rate (ECAR) diminished with 2-DG treatment in all cases. A decrease in OCR was observedin pLL-stimulated BMDCs treated with oligomycin. SCENITH assays showed that cells stimulated withHF obtained their energy primarily from glycolysis, with minimal mitochondrial dependence. In contrast,pLL-stimulated BMDCs showed greater amino acid and fatty acid oxidation capacities (n = 3, ***p<0,001HF or pLL vs. control).Conclusion: E. granulosus antigen recognition induces metabolic reprogramming in BMDCs thatdirectly impact in their cell function and immune response against the parasite.